Samuel Beckett : the art of rhetoric - Morot-Sir, Edouard; Harper, Howard; McMillan, Dougald (North Carolina studies in the Romance languages and literatures. Symposia, 2018)
Collected essays from a symposium held in April 1974, at the University of North Carolina at Chapel Hill, this volume analyzes Beckett's philosophy, rhetoric, poetry, and novels.